Peningkatan Kinerja Organisasi Melalui Kepemimpinan Spiritual, Green HRM dan Percieved Organizational Support - Kasmawati, Yuni; Karjono, Karjono (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
In the current era of globalization, the business world is required to provide environmental and social protection regarding its products and services. Consumers apart from wanting the services and products they need, also want their products and services to have no impact on the environment and society. To achieve competitive and sustainable advantage, environmentally friendly business management is the solution. This research aims to analyze the role of perceived organizational support in moderating the influence of spiritual leadership and green human resource management on organizational performance. The research population was employees at shipping companies in South Jakarta. A sample of 100 respondents was taken using random sampling technique. Data was collected through questionnaires. Data analysis uses the SEM-PLS approach. The research results found that spiritual leadership and Green human resource management directly have a significant influence on organizational performance. Perceived organizational support has not been able to strengthen the influence of spiritual leadership and green human resource management on organizational performance.